Development of a matrix reference material for amoxicillin in lyophilized bovine milk - LIU Tian-he; WEI Ning; WU Cai-hong; ZHANG Yu; LIU Qiu-hui (Shipin yu jixie, 2023)
Objective： This study aimed to provide the basis of quantity traceability for the analysis of amoxicillin residues in milk. At the same time, it can also provide quantity standards for ensuring the effective implementation of amoxicillin monitoring in milk and combating the abuse of amoxicillin in the country and regions. Methods： Two healthy middle-class dairy cows were injected with amoxicillin intramuscularly. After the natural metabolism of the drug for a period of time, the milk containing the target drug amoxicillin was collected and made into milk matrix reference material containing amoxicillin by vacuum freeze-drying technology. The uniformity test, stability test, fixed value and uncertainty evaluation of the prepared milk lyophilized powder matrix reference material were carried out. Results： In the uniformity test, the F value obtained is 0.05, The results showed that the preparation of the standard milk powder was homogeneous; In the stability test, the short-term stability test （25, 4, -20 ℃; 2 weeks） and long-term stability test （4, -20 ℃; 6 months） showed good stability;The reference materials were jointly calibrated by 8 laboratories, and the final calibration result was 4.05 μg/kg, the total uncertainty being 0.2 μg/kg. Conclusion： The prepared amoxicillin matrix reference material in milk freeze-dried powder has good uniformity and stability, which can be used as a carrier to trace the amount of amoxicillin in milk, and can be widely used in the methodology verification and quality control of amoxicillin detection in milk.